Pengaruh Pemberdayaan Usaha Kecil Terhadap Peningkatan Pendapatan Usaha di Kecamatan Singkil Kota Manado - Jacobs, Feiby Pisga; Posumah, Jhonny Hanny; Dengo, Salmin (Sam Ratulangi University, 2015)
Small business sector has been recognized as having a vital role in proving the nationseconomy. Because it is expected the government can give special attention to small businesses. Thisneeds to be done by the government because most businesses in Indonesia belloging to smallbusinesses. The phenomenon of the low quality of human resources for small businesses almostuniformly in all regions of Indonesia. This applies also for those belonging to small businesses in thedistrict. Because it attemps to foster the entrepereneurial spirit for small businesses is something thatshould be done to increase growth have to a little better so as to change the status of its business at thesame effect on the increase in their income.This study aimed to analyzed the relationship between theempowerment of small businesses to increase revenues in the District of Singkil in Manado City byusing purposive sampling and analysis of how to carry out the data collection isquestioner.Intepolation methods in order to predict the value of the variable income of smallbusinesses (Y) (Sudjana, 1983). By using statistical tools for data processing assisted by computersthrought the program SPSS version 20 for Windows.Factors strengthening human resources throughtthe provision of the venture capital loans partially contribute positively and significantly to the incomeof the small businesses.Keyword: Empowering Small Businesses, Increase Revanues